Decentralization: Managerial Ambiguity by Design. - Burns, Thomas J.; Colson, Robert H. (The Accounting Review, 1981)
Reviews the book "Decentralization: Managerial Ambiguity by Design," by Richard F. Vancil and Lee E. Buddrus.